Prevalence and Associated Risk Factors of Chronic Kidney Disease among Individuals Attending a Screening Camp in Rupandehi District, Nepal: A Cross-Sectional Study - Basnet, Shakti; Khanal, Sushil; Adhikari, Bimanchal; Bhusal, Priya; Parajuli, Aabishkar; khadka, Aarju; Ghimire, Madhav (Journal of Bharatpur Hospital, 2026)
Background Chronic kidney disease (CKD) is an emerging public health problem in globally, often detected late due to a lack of screening. Early identification through community-based screening camps can help in estimating the burden and associated risk factors. This study aimed to find the prevalence of CKD and its associated factors of CKD among individuals attending a screening camp in the Butwal area of Rupandehi District of Nepal. Methods A community based cross sectional study was conducted from 28th to 31st October 2025 in Butwal, Lumbini Province, Nepal. The screening camp was organized by Siddhababa Hospital and Research Center Pvt. Ltd. with support from the Nepal kidney foundation and Bridge of life USA. A total of 947 participants of all age groups were included. Data were collected using a structured questionnaire, consisting of anthropometric measurements, urine analysis, and serum creatinine for estimation of eGFR. CKD was defined based on reduced eGFR and/or markers of kidney damage. Data were analyzed using SPSS, and Chi-square test was used to assess associations. P-value <0.05 was considered statistically significant. Results The prevalence of CKD was 32.1% (with 95% CI as 29.13%-35.18%). The statistically significant variables associated with CKD are age (p<0.001), BMI (p<0.001), Diabetes (p=0.042), Antihypertensive medication use (p<0.001), Antidiabetic medication use (p=0.008), proteinuria (p=0.014), abnormal creatinine (p<0.001), abnormal eGFR (p=0.02), and urine pH (p<0.001). Conclusions CKD prevalence was high among screening camp participants, with significant associations with age, obesity, diabetes, and renal function markers. Community-based screening and early detection strategies are essential for the prevention and control of CKD in Nepal.